STUDY ON THE OPERATION OF THE THERMOELECTRIC POWER PLANTS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Cristinel RACOCEANU (Fiabilitate şi Durabilitate)
This paper presents a case study on the technical measures applied in the thermoelectric power plants in order to achieve an ecological functioning. Sustainable development implies the adaptation of Romanian thermoelectric power plants to the European Union requirements for environmental protection. The results of the experimental measurements of the thermoelectric power plant pollutants, which comprise 330 MW energy groups, are presented. There are presented the technical measures that lead to the sustainable development of the Romanian thermal power plants, the influence of the energy efficiency of the steam boiler of the 330 MW energy group on the environment.